Characterization of the toxin Plx2A, a RhoA‐targeting ADP‐ribosyltransferase produced by the honey bee pathogen Paenibacillus larvae. (5th December 2017) - Ebeling, Julia; Fünfhaus, Anne; Knispel, Henriette; Krska, Daniel; Ravulapalli, Ravikiran; Heney, Kayla A.; Lugo, Miguel R.; Merrill, A. Rod; Genersch, Elke
Summary: The toxin Plx2A is an important virulence factor of Paenibacillus larvae, the etiological agent of American Foulbrood, the most destructive bacterial disease of honey bees. Biochemical and functional analyses as well as the crystal structure of Plx2A revealed that it belongs to the C3 mono‐ADP‐ribosylating toxin subgroup. RhoA was identified as the cellular target of Plx2A activity. The kinetic parameters ( K M, k cat ) were established for both the transferase and glycohydrolase reactions. When expressed in yeast, Plx2A was cytotoxic for eukaryotic cells and catalytic variants confirmed that the cytotoxicity of Plx2A depends on its enzymatic activity. The crystal structure of Plx2A was solved to 1.65 Å and confirmed that it is a C3‐like toxin, although with a new molecular twist, it has a B‐domain. A molecular model of the 'active' enzyme conformation in complex with NAD + was produced by computational methods based on the recent structure of C3bot1 with RhoA. In murine macrophages, Plx2A induced actin cytoskeleton reorganization while in insect cells, vacuolization and the occurrence of bi‐nucleated cells was observed. The latter is indicative of an inhibition of cytokinesis. All these cellular effects are consistent with Plx2A inhibiting the activity of RhoA by covalent modification.